'It was a departure of sorts': glocal homes in recent short fiction by Chimamanda Ngozi Adichie, Efemia Chela, Chibundu Onuzo and Lesley Nneka Arimah. Issue 2 (4th March 2023) - Terry, Jennifer
ABSTRACT: This article takes off from two of the angles of contention found in critical responses to Paul Gilroy's The Black Atlantic and subsequent Atlanticist studies: asymmetries and exclusions along gender lines, and insufficient attention to the dynamics of contemporary global capital. It examines what gets articulated when recent African short fiction is approached via a frame centered on the location of home, gendered labour, sexual and reproductive economies, and the interrelation of the domestic and capitalism. In particular, it is informed by Alexis Pauline Gumbs's counter-heuristic to Gilroy, the Black Feminine Domestic. Gumbs's attempt to make visible such a subject position and forms of labour prompts my focus on domestic workers and analogous figures, often migrant and low paid and sometimes found only at the edges of texts. I discuss Efemia Chela's 'Chicken' (2014), Chibundu Onuzo's 'Sunita' (2015), Lesley Nneka Arimah's 'Skinned' (2019), and, from Chimamanda Ngozi Adichie's collection The Thing Around Your Neck (2009), the stories 'Imitation, ' 'The Thing Around Your Neck' and 'On Monday of Last Week.' Here the tropes of circulation and regimes of rationality identified by Gilroy find counterparts in the structuring of workforces, the reach of body and biopolitics, and discourses of national borders and migration. The lens of 'women's work' permits an intersectional shift in and beyond Black Atlantic frames and the heteropatriarchal imagination, but the selected material and preoccupations here also seek to offer another opening on debates about, and genres of, 'African' writing.